A comparison of cardiovascular risk factors for ten antipsychotic drugs in clinical practice - Bodén R (Dove Medical Press, 2013)
Robert Bodén,1,2 Gunnar Edman,3,4 Johan Reutfors,2 Claes-Göran Östenson,3 Urban Ösby3,4 1Department of Neuroscience, Psychiatry, Uppsala University, Uppsala, Sweden; 2Department of Medicine Solna, Centre for Pharmacoepidemiology, Karolinska Institutet, Stockholm, Sweden; 3Department of Molecular Medicine and Surgery, Karolinska Institutet, Stockholm, Sweden; 4Department of Psychiatry, Tiohundra AB, Norrtälje, Sweden Abstract: It is well known that abdominal obesity, dyslipidemia, and insulin resistance are highly prevalent in patients receiving maintenance treatment with antipsychotics, but there is limited knowledge about the association between cardiovascular risk factors and treatment with antipsychotic drugs. In this naturalistic study we investigated a sample of 809 antipsychotic-treated patients from Swedish psychosis outpatient teams. Cardiovascular risk factors (eg, metabolic syndrome, homeostasis model assessment of insulin resistance, and low-density lipoprotein values) were measured, and their associations to current antipsychotic pharmacotherapy were studied. Ten antipsychotic drugs were compared in a stepwise logistic regression model. For the patients, the presence of the components of metabolic syndrome ranged from 35% for hyperglycemia to 64% for elevated waist circumference. Hypertriglyceridemia was associated with clozapine (odds ratio [OR] = 1.81, 95% confidence interval [CI] 1.08–3.04), reduced high-density lipoprotein with both clozapine and olanzapine (OR = 1.73, 95% CI 1.01–2.97; and OR = 2.03, 95% CI 1.32–3.13), hypertension with perphenazine (OR = 2.00, 95% CI 1.21–3.59), and hyperglycemia inversely with ziprasidone (OR = 0.21, 95% CI 0.05–0.89) and positively with haloperidol (OR = 2.02, 95% CI 1.18–3.48). There were no significant relationships between any of the antipsychotic drugs and increased waist circumference, homeostasis model assessment of insulin resistance, or low-density lipoprotein levels. In conclusion, treatment with antipsychotic drugs is differentially associated with cardiovascular risk factors, even after adjusting for waist circumference, sex, age, and smoking. Keywords: adverse metabolic effects, antipsychotic drugs, cardiovascular risk factors, HOMA-IR, metabolic syndrome